Factors Affecting Employment Opportunities to Manufacturing Sector of Nepal - Dhungel, Bashu Dev; Lamichhane, Pitambar (Economic Review of Nepal, 2021)
Nepalese manufacturing sector is not properly developed. However, manufacturing sector provides wide employment opportunities to people. Therefore, the main purpose of this study is to investigate the factors affecting employment opportunities in Nepalese manufacturing sector. This paper has employed two stage least square (2SLS) method using the time series macroeconomic data. The 2SLS method has been used to avoid the simultaneous equation bias. Manufacturing employment is explained variable and real foreign direct investment, manufacturing gross domestic product, NEPSE index and government expenditure in manufacturing sector are considered as explanatory variables. The 2SLS results have confirmed that foreign direct investment flows, capital market development, government expenditure and real GDP are positive and significant factors which contribute to expand the employment opportunities in manufacturing sector of Nepal. Therefore, Government of Nepal rise the expenditure in manufacturing sector as well as others infrastructure development to increase the flows of foreign capital in manufacturing sector to generate the employment opportunities. Furthermore, government of Nepal focus to develop financial markets for capital creation which leads economic growth as well as employment opportunities.